The Impact of Social Media Usage on Social English Among Generation Z: A Literature Review - Azhari, Teuku; Sahputri, Juwita; Kurniawati, Kurniawati; Rizki, Dini (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Social media has become an integral part of Generation Z's lives, raising questions about its impact on their social English skills. Through a systematic literature review, we aim to reveal the impact of social media use on Generation Z's social English. Research findings show that social media has a mixed impact on Generation Z's social English skills. This can be both beneficial and detrimental. On the positive side, it helps grow social English through engagement with influencers and content. On the negative side, issues such as information overload, FOMO, imitation of inappropriate content, and mental health problems can harm social English skills. Additionally, it influences communication styles through the widespread use of emojis, acronyms and emoticons. This must be balanced with proficiency in formal social English for effective communication.